Fault detection based on interval observers and dynamic event-triggered fault-tolerant control for morphing aircraft - Fu, Xingjian; Wang, Xiaohan (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a fault detection mechanism using interval observers and a robust fault-tolerant control strategy with dynamic event-triggered mechanism are designed for the switched control problem during the transformation process of a morphing aircraft. Firstly, an interval observer design method for the nonlinear switched system is given.
Keywords: morphing aircraft; interval observer; fault detection; dynamic event-triggered; robust fault-tolerant control; switched systems